2011
DOI: 10.1002/ajmg.a.34045
|View full text |Cite
|
Sign up to set email alerts
|

Isolated oligodontia associated with mutations in EDARADD, AXIN2, MSX1, and PAX9 genes

Abstract: Oligodontia is defined as the congenital lack of six or more permanent teeth, excluding third molars. Oligodontia as well as hypodontia (lack of one or more permanent teeth) are highly heritable conditions associated with mutations in the AXIN2, MSX1, PAX9, EDA, and EDAR genes. Here we define the prevalence of mutations in the AXIN2, MSX1, PAX9, EDA, and EDAR genes, and the novel candidate gene EDARADD in a cohort of 93 Swedish probands with non-syndromic, isolated oligodontia. Mutation screening was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 43 publications
5
104
0
3
Order By: Relevance
“…25 MSX1 and non-syndromic tooth agenesis Non-syndromic tooth agenesis (ns TA) is another common developmental anomaly that can be caused by MSX1 variants. 14 To date, nearly 20 MSX1 mutations have been related to ns TA 8,13,[26][27][28][29][30][31][32][33][34][35][36][37] (Table 2). Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…25 MSX1 and non-syndromic tooth agenesis Non-syndromic tooth agenesis (ns TA) is another common developmental anomaly that can be caused by MSX1 variants. 14 To date, nearly 20 MSX1 mutations have been related to ns TA 8,13,[26][27][28][29][30][31][32][33][34][35][36][37] (Table 2). Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…Axin1 was found to be methylated in a pair of discordant monozygotic twins with caudal duplication anomaly (OMIM: 607864) (337). Supporting the critical role of Axin2 in craniofacial development, multiple studies in humans have identified polymorphisms/mutations in Axin2 related to tooth agenesis (338)(339)(340)(341) and oral clefts (132,340). Mutations in Axin2 are also associated with oligodontia-colorectal cancer syndrome (Arg656X) (OMIM: 608615) (338).…”
Section: Axinmentioning
confidence: 99%
“…1 As tooth formation shares mechanisms with the development of other ectodermal appendages, TA often occurs as part of a variety of ectodermal dysplasia (ED) syndromes including Witkop syndrome, hypohydrotic ectodermal dysplasia, odonto-onycho-dermal dysplasia (OODD), Schöpf-Schulz-Passarge syndrome (SSPS) and others. For these human TA syndromes, mutations have been identified, respectively, in MSX1, 2 EDA, EDAR, 3-5 EDARADD, 6 and WNT10A. 7,8 WNT10A mutations were identified in a family of which four members were affected with isolated TA or microdontia, 9 whereas more recently in a larger cohort of 34 patients with isolated TA, 56% appeared to have WNT10A mutations.…”
Section: Introductionmentioning
confidence: 99%